Pengaruh Penggunaan Chat GPT terhadap Minat Belajar Mahasiswa - Risatun Nada; Kamelia Kamelia; Muhammad Rifky; Muhammad Sulaiman (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
One of the technologies that is currently widely used is ChatGPT, a chatbot that utilizes AI in its operations. One of the impacts that needs to be considered is the decline in students' interest in reading. Students' interest in learning can decrease due to the convenience offered by ChatGPT through services that use natural human language. The purpose of this study is to determine and analyze the effect of using ChatGPT on students' interest in learning and to identify other factors that can affect students' interest in learning. Overall, the use of Chat GPT technology in education has great potential to improve the quality of teaching and learning. However, the challenges associated with the use of this technology also need to be handled properly so that it can be used optimally and does not have a negative impact on the educational process. The use of Chat GPT can make it easier for users to understand and obtain information so that it helps learning activities, but on the other hand, the use of technology, in this case Chat GPT, needs to be used wisely in order to uphold the values ​​of honesty and originality in the academic world. Hopefully, more technology will be present as facilities that can help students' learning activities so that the presence of technology can have a positive effect on their interest in learning.